Analisis penyerapan tenaga kerja di Provinsi Jawa Tengah - Kawasaki, Putri (Economics, Finance, and Business Review, 2024)
Labor absorption is still one of the problems faced by Central Java Province. This study aims to explore the influence of Gross Regional Domestic Product, Regional Minimum Wage, Foreign Investment, Domestic Investment, and Government Expenditure on the level of labor absorption in Central Java. This study analyzes 35 regencies/cities in Central Java in the period 2017 to 2022. The analytical method applied is panel data regression analysis. The findings show that Gross Regional Domestic Product, Regional Minimum Wage, and Foreign Investment have a positive influence on labor absorption in Central Java Province. Conversely, Domestic Investment, Government Expenditure, and COVID-19 do not affect labor absorption in Central Java Province. The results of the study show that GRDP has a major influence on labor absorption. The implication is that regional governments must encourage infrastructure investment, development of productive sectors, and increase regional competitiveness to encourage economic growth so that labor absorption increases.